Motivational And Structural Barriers In Low Tahfiz Program Interest: Hambatan Motivasi Dan Struktural Dalam Minat Program Tahfiz Rendah - Aan Ibnu Sabil; Fatma Sari; Darnanengsih Darnanengsih (Halaqa: Islamic Education Journal, 2026)
General Background Tahfiz programs are central to Islamic education because they support Qur’an memorization, religious character formation, and students’ sustained engagement with Islamic values. Specific Background In Islamic secondary education, student participation in Qur’an memorization programs remains a persistent challenge, particularly when learners participate because of external pressure rather than personal willingness. Knowledge Gap Previous studies have largely emphasized memorization outcomes, program management, and quantitative motivational factors, while students’ subjective experiences, peer dynamics, and internal-external causes of disengagement in the Madrasah Aliyah context remain insufficiently explored. Aims This study aimed to analyze internal and external factors contributing to students’ low interest in participating in the Qur’an memorization program. Results The findings show that most students joined the program due to obligation rather than intrinsic motivation, with only a few demonstrating self-initiated participation. Internal barriers included weak Qur’anic reading fluency, low confidence, embarrassment during recitation, and limited learning autonomy. External barriers included minimal parental support, demotivating peer dynamics, monotonous instructional practices, limited tahfiz teaching staff, and short memorization sessions of approximately 15 minutes. Novelty This study identifies peer-group dynamics and basic Qur’anic literacy insecurity as important demotivating factors within tahfiz learning. Implications The findings suggest the need for small-group talaqqi, systematic muraja’ah routines, literacy screening, teacher mentoring cycles, and stronger school-family communication to improve student participation. Highlights • Most learners joined the program through obligation rather than personal initiative.• Weak Qur’anic reading fluency reduced confidence during recitation activities.• Family support, peer climate, teaching variation, and session duration shaped disengagement. Keywords Tahfiz Interest; Qur’an Memorization; Student Motivation; Structural Barriers; Islamic Education